Disparities in sleep characteristics by race/ethnicity in a population-based sample: Chicago Area Sleep Study - Carnethon, Mercedes R.; De Chavez, Peter John; Zee, Phyllis C.; Kim, Kwang-Youn A.; Liu, Kiang; Goldberger, Jeffrey J.; Ng, Jason; Knutson, Kristen L. (Sleep medicine, 2016)
•This was the largest epidemiologic study to include objective determination of sleep in a multiethnic population of Black, Asian, Hispanic, and White participants.•Adverse sleep characteristics were observed in Black participants as compared with White participants.•Despite similar cardiovascular risk profiles, Asian participants reported more daytime sleepiness than did Whites. Prior studies report less favorable sleep characteristics among non-Whites as compared with non-Hispanic Whites. However, few population-based studies have used objective measures of sleep duration, especially in more than two racial/ethnic groups. We tested whether objectively estimated sleep duration and self-reported sleep quality varied by race and whether differences were at least partially explained by the variability in clinical, psychological, and behavioral covariates. Adults aged 35–64 years who self-identified as White, Black, Asian, or Hispanic were randomly sampled from Chicago, IL, and the surrounding suburbs. Our analytic sample included adults who had an apnea–hypopnea index <15 after one night of screening and who completed seven nights of wrist actigraphy for determination of sleep duration, sleep percentage, minutes of wake after sleep onset, and sleep fragmentation (n = 495). Daytime sleepiness was estimated using the Epworth Sleepiness Scale (ESS), and sleep quality was estimated from the Pittsburgh Sleep Quality Index (PSQI). Following statistical adjustment for age, gender, education, work schedule (ie, day vs. night shift), smoking status, depressive symptoms, body mass index (BMI), hypertension, and diabetes, sleep duration (minutes) was significantly (all p < 0.01) shorter in Black (mean = 399.5), Hispanic (mean = 411.7), and Asian (mean = 409.6) participants than in White participants (mean = 447.4). All remaining sleep characteristics were significantly less favorable among Black participants as compared with White participants. Asian participants also reported significantly more daytime sleepiness than did White participants. Differences in sleep characteristics by race/ethnicity are apparent in a sample of adults with a low probability of sleep apnea and following adjustment for known confounders.